Relationship between Nurses' Plateau and Job Burnout in Kerman Private Hospitals in 2014 - Malikeh Beheshtifar (Tehran University of Medical Sciences, 2017)
Background and Aim: Job burnout is a painful experience for individuals and it is a costly phenomenon for organizations. Plateau is a key aspect for increasing this problem. The aim of this study was to investigate the relationship between nurses' plateau and job burnout in Kerman private hospitals in 2014. Materials and Methods: In this study, the descriptive, correlational and cross-sectional methods was used. The study population consisted of 142 nurses in Arjomand and Razieh-Firoz hospitals. According to Morgan table, 100 nurses were selected as the sample size. Two questionnaires was used: the plateau questionnaire with content validity 0.98 and reliability 0.94 and the job burnout one with content validity 0.98 and reliability 0.93. To analysis data, partial least squares (PLS) with Smart PLS 2 software was used. Results: The results showed that there was a significant relationship between nurses' plateau including components of hierarchical plateau and job content plateau with their job burnout in Arjomand and Razieh-Firoz hospitals. Conclusion: Job burnout has destructive effects on individuals' performance; so, it is important to prevent it in the organizations. One of its aggravating factors is plateau. It is suggested to decrease the plateau at workplace by creating the good work condition, efficiency sense, individual progress sense, and chance to promotion.